The policy of energy management in public buildings procurements through the study of the process of delegated project management - Case of Morocco. (June 2022) - El Asri, Najat; Nouira, Youness; Maaroufi, Ibtissam; Marfak, Abdelghafour; Saleh, Nour; Mharzi, Mohammed
Abstract: Given the exemplary of public buildings, energy efficiency in these buildings is an essential element in the response of societies to the challenges of climate change, economic development, and energy security. Although there is a lot of literature about different policies to promote energy efficiency in buildings and particularly in tertiary buildings, insufficient attention has been given to promote it through the building authorization process. This work attempts to establish a new method for achieving energy efficiency in the public buildings by integrating this aspect into the monitoring and controlling processes that delivers this kind of buildings in Morocco; specifically, the delegated project management, through the analysis of the process, and the identification of priority policies or actions. Through surveys with experts, we proposed to analyse the authorization process, to model it, and to highlight the different policies by which Energy Efficiency can be integrated or improved in this process. Our original contribution is to explore a new method to reach energy efficiency in the public buildings without any additional technical actions, but rather with an optimal approach. Highlights: A policy outlining a practical framework for design and implementation of energy efficient public buildings was presented. A list of policies to promote energy efficiency in public building procurement is presented and prioritized. The authorization process for new public buildings was modelled. Energy management in public buildings is a complex and multidimensional task. A qualitative study was transformed into quantitative findings.